PENARIKAN DIRI AMERIKA SERIKAT DARI KEANGGOTAAN KOMISI PENGUNGSI INTERNASIONAL (UNITED NATIONS HIGH COMMISSIONER FOR REFUGEES) SUATU TINJAUAN HUKUM INTERNASIONAL - Hengki Hengki; Suhaidi Suhaidi; Jelly Leviza (Journal of USU International Law, 2019)
ABSTRACT Hengki* Prof. Dr. Suhaidi, S.H, M.H** Dr. Jelly Leviza, S.H, M.Hum*** The intensity of relations between countries in the world today is very high. Collaborations established by each countries are an effort to realize the national interests of the country. A forum for building relationships with other countries is known as International Organizations. The International Organizations are formed by the exixtence of a joint agreement that contain the rights and obligations of member countries, one of them is in terms of withdrawal from membership of International Organization. The problem of withdrawal from The United Nations High Comissioner for Refugees (UNHCR) membership is regulated in the 1951 Convention on the Status of Refugees and The Additional Protocol of 1967 is not widely regulated that in the end each country has the possibility of withdrawing. Therefore, the method used in this thesis is normative legal research which is a methid conducted on applicable legal norms, both originating from national law and international law. The normative research method is a scientific procedure for finding truth based on legal scientific logic from the normative law and the nature of research are descriptive analytical which describes national legal norms and norms of international law, related to United States withdrawal from United Nations High Comissioner for Refugees (UNHCR) membership as an International Organization. Analysis of United States withdrawal from United Nations High Comissioner for Refugees (UNHCR) membership and The New York Agreement Declaration of Refugees and Migrants under the International Law refers to article 54 of the 1986 Vienna Convention stating that withdrawal can be carried out if it is included in the relevant international agreement or can be carried out at anytime. Futhermore, it is also explained in the provisions of Article 44 Paragraph (1) of the 1951 Convention on the Status of Refugees that states every country that has become a member can cancel this convention at anytime with a notification submitted to the General Secretary of the United Nations. Thus, the actions and steps taken by the United States in this case have gone through appropriate procedures even though the act of with drawal is considered to indicate a lack of a strong commitment to overcome global problem. Key Word : International Organization, UNHCR, Vienna Convention 1986, United States, Withdrawal.